Chemical composition of essential oil from two species of Pulsatilla growing wild in Northern Kazakhstan - Kirillov, V.Yu.; Stikhareva, T.N.; Serafimovich, M.V.; Mukasheva, F.T.; Gering, A.V.; Sarsenbaeva, L.A.; Atazhanova, G.A.; Adekenov, S.M. (Publ.KarSU, 2018)
The aim of the study was to investigate for the first time the chemical composition of the essential oil from plant species of the genus Pulsatilla of the family Ranunculaceae Juss. — P. flavescens (Zucc.) Juz. and P. patens (L.) Mill. growing wild in Northern Kazakhstan. The essential oil was obtained from the dried aerial parts of the plants (stems, leaves, flower heads) by hydrodistillation for 6 hours without steeping in distilled water and with preliminary steeping in distilled water for 14 hours. The qualitative and quantitative compositions of the specimens of the essential oils were analyzed by the method of GC-MS. The main constituents of P. flavescens and P. patens essential oil were tricosane (30.9–47.3 % and 45.6 % without steeping in distilled water and 40.4–50.1 % and 32.9 % with steeping in distilled water for 14 hours), heneicosane (22.1–31.8 % and 31.5 % without steeping in distilled water and 20.9–30.4 % and 26.6 % with steeping in distilled water for 14 hours), 2-pentadecanone (11.6–33.8 % and 10.8 % without steeping in distilled water and 6.3–10.1 % and 19.2 % with steeping in distilled water for 14 hours), respectively. The results suggested that the essential oil of P. flavescens and P. patens can have the antimicrobial properties.
Солтүстік Қазақстанда өсетін Pulsatilla екі түрлерінің эфир майларының химиялық құрамы
Химический состав эфирного масла двух видов Pulsatilla, произрастающих в Северном Казахстане
Keywords: Pulsatilla; essential oil; tricosane; heneicosane; 2-pentadecanone